Telementoring and Homeschooling during School Closures: A Randomized Experiment in Rural Bangladesh - Hashibul Hassan; Asad Islam; Abu Siddique; Liang Choon Wang (Institute of Labor Economics (IZA), 2023)
Using a randomized experiment in 200 Bangladeshi villages, we evaluate the impact of an over-the-phone learning support intervention (telementoring) among primary school children and their mothers during Covid-19 school closures. Post-intervention, treated children scored 35% higher on a standardized test, and the homeschooling involvement of treated mothers increased by 22 minutes per day (26%). We also found that the intervention forestalled treated children's learning losses. When we returned to the participants one year later, after schools briefly reopened, we found that the treatment effects had persisted. Academically weaker children benefited the most from the intervention that only cost USD 20 per child.
Keywords: C93; I21; I24; 330; randomized experiment; primary education; school closure; COVID-19; homeschooling; telementoring; rural Bangladesh